Correlation between BMPR1B Gene Polymorphism and some Reproductive Traits in Awassi Sheep - Ayman Hashem Essa.; T. R. , Mohammed; N. N. Al-Anbari (مجلة الانبار للعلوم البيطرية, 2024)
The (BMPR-1B) gene is one of the main genes for ewe fertility. This study was conducted to check the association between BMPR-IB gene polymorphisms and some traits of Awassi. This study was made in Anbar Governorate - (Agricultural Research Department) Al-Dawar. Date of experience collected from 34 ewes at the age of 4-6 years. Next, DNA was extracted and a PCR reaction was performed to amplify blood samples taken from the ewes to confirm the presence of the BMPR1B gene. The sequence was determined using Sanger sequencing technology. The data were then analyzed and compared between sample sequences to determine SNPs, genotype frequencies, allele frequencies, and their association with reproductive and growth traits. The results showed mutations in the heteroplasmy site rs410310346 (T>C) and rs592447725 (G>A). The results indicated that the TC genotype at the mutation site rs410310346 (T>C) was significantly superior (P≤0.05) in ewes whose rates of fertility and body length were higher compared to the CC genotype. The genotypes haven’t got an important effect on the proportion of twins, fertility rate, chest circumference, front height, ewe birth weight, and lamb weight at birth. The relationship of genotype GG and GA at the mutation site rs592447725 (G > A) showed a very significant effect (P≤0.01) on the percentage fertility rate and a noteworthy result (P≤0.05) on body length, height at the front and birth weight of lambs, but there isn’t a big impact. In the percentage of twins, fertility rate, chest circumference, and birth weight of ewes. Therefore, the effect of the BMPR1B gene can be used as a genetic marker to select ewes with good genotypes to improve herd performance.